2019
DOI: 10.1007/s11357-019-00097-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related alterations of articular cartilage in pituitary adenylate cyclase–activating polypeptide (PACAP) gene–deficient mice

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is an evolutionarly conserved neuropeptide which is produced by various neuronal and non-neuronal cells, including cartilage and bone cells. PACAP has trophic functions in tissue development, and it also plays a role in cellular and tissue aging. PACAP takes part in the regulation of chondrogenesis, which prevents insufficient cartilage formation caused by oxidative and mechanical stress. PACAP knockout (KO) mice have been shown to display early aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…One of the possible protective agents could be PACAP, which has been described to have a preventive effect on AD formation (Han et al, 2014b). PACAP has also been shown to modify amyloid aggregation (Reglodi et al, 2018c) and has important preventive functions in aging (Reglodi et al, 2018a;Szegeczki et al, 2019). The general protective role of the neuropeptide has been demonstrated in various disorders, such as retinopathy (Vaczy et al, 2018), diabetes (Banki et al, 2014), Parkinson's disease (Reglodi et al, 2006;Reglodi et al, 2017), and inflammatory processes (Sakamoto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the possible protective agents could be PACAP, which has been described to have a preventive effect on AD formation (Han et al, 2014b). PACAP has also been shown to modify amyloid aggregation (Reglodi et al, 2018c) and has important preventive functions in aging (Reglodi et al, 2018a;Szegeczki et al, 2019). The general protective role of the neuropeptide has been demonstrated in various disorders, such as retinopathy (Vaczy et al, 2018), diabetes (Banki et al, 2014), Parkinson's disease (Reglodi et al, 2006;Reglodi et al, 2017), and inflammatory processes (Sakamoto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PACAP and its receptors have been detected in the CNS and many peripheral tissues such as the respiratory tract, urinary tract, and digestive system (Vaudry et al, 2009), or in bone and chondrogenic cultures (Juhasz et al, 2015a;Jozsa et al, 2018). The protective/preventive role of PACAP has been proven in several age-related disorders, and lack of PACAP leads to accelerated aging (Reglodi et al, 2018a;Szegeczki et al, 2019). PACAP has been shown to attenuate the severity of AD in different animal models and protects from Aβ toxicity (Han et al, 2014a;Maasz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage, which contains no blood vessels, nerves, or lymphatics, has long been considered inert tissue in the body. However, an increasing number of studies have shown that cartilage is also regulated by sensory nerves, and sensory neuropeptides can be involved in the regulation of cartilage physiological and pathological metabolism by affecting the proliferation, differentiation, and secretion of chondrocytes (17)(18)(19)(20). Although SP and its receptors are widely distributed in the locomotor system, its effects on bone and cartilage metabolism are not well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…It affects tear secretion (Nakamachi et al 2016), influences muscle responses of the iris (Yamaji et al 2005), increases blood flow in the eye (Dorner et al 1998) and regulates pigment epithelial cell functions (Fabian et al 2012(Fabian et al , 2019Maugeri et al 2019a). Most importantly, as a general protective peptide found not only in the central nervous system but several peripheral organs as well (Laszlo et al 2019;Liu et al 2019;Polanco and Pennuto 2018;Reglodi et al 2018d, e;Shioda et al 2019;Szegeczki et al 2019), PACAP has been shown to exert diverse retinoprotective effects in models of toxic, ischemic, inflammatory and traumatic retinal injuries (Atlasz et al 2016(Atlasz et al , 2019Cheng et al 2018;Endo et al 2011;Gabriel et al 2019;Kvarik et al 2016;Seki et al 2008;Szabadfi et al 2016;Vaczy et al 2016;Ye et al 2019a, b). Several retinal cell types can be protected by PACAP, including ganglion cells, bipolar neurons, amacrine and pigment epithelial cells (Atlasz et al 2008;Fabian et al 2019;Maugeri et al 2019a;Szabadfi et al 2012).…”
Section: Introductionmentioning
confidence: 99%